Bishop John Vitez and Early Renaissance Central Europe The Humanist Kingmaker - Matić, Tomislav (Beyond Medieval Europe, 2022)
The subject of this study is the life, career, and public activities of John Vitez of Sredna (early 1400s-1472)-a politician, prelate, diplomat and one of the most influential personages in the history of Renaissance humanism in the medieval Kingdom of Hungary. Vitez was a nobleman from medieval Slavonia, who had spent a large portion of his lifetime as the bishop of Oradea (1445-1465), and finished his career and his life as the archbishop of Esztergom and primate of Hungary (1465-1472). He is also the author of the only extant complete collection of letters from the late medieval Kingdom of Hungary. His life is relevant to the history of Hungary, Croatia, Bohemia, Poland, and the wider Central European area. This work studies the existing literature on John Vitez, presents new sources on his life and career, and attempts to create a complete image of him within the context of the tumultuous history of early Renaissance Central Europe.